Anti-Neurotrophic Effects from Autoantibodies in Adult Diabetes Having Primary Open Angle Glaucoma or Dementia - Zimering, Mark B.; Moritz, Thomas E.; Donnelly, Robert J. (Frontiers in Endocrinology, 2013)
Aims: To test for anti-endothelial and anti-neurotrophic effects from autoantibodies in subsets of diabetes having open- angle glaucoma, dementia or control subjects. Methods: Protein-A eluates from plasma of 20 diabetic subjects having glaucoma or suspects and 34 age-matched controls were tested for effects on neurite outgrowth in rat pheochromocytoma PC12 cells or endothelial cell survival. The mechanism of the diabetic glaucoma autoantibodies' neurite inhibitory effect was investigated in coincubations with the selective Rho kinase inhibitor Y27632 or the sulfated proteoglycan synthesis inhibitor sodium chlorate. Stored protein-A eluates from certain diabetic glaucoma or dementia subjects which contained long-lasting, highly stable cell inhibitory substances were characterized using mass spectrometry and amino acid sequencing. Results: Diabetic primary open angle glaucoma or suspects (n=20) or diabetic dementia (n=3) autoantibodies caused significantly greater mean inhibition of neurite outgrowth in PC12 cells (p < .0001) compared to autoantibodies in control diabetic (n=24) or nondiabetic (n=10) subjects without glaucoma (p < .01). Neurite inhibition by the diabetic glaucoma autoantibodies was completely abolished by 10 µM concentrations of Y27632 (n=4). It was substantially reduced by 30 mM concentrations of sodium chlorate (n=4). Peak, long-lasting activity survived storage x 5 years at 0-4 deg C and was associated with a restricted subtype of Ig kappa light chain. Diabetic glaucoma or dementia autoantibodies (n=5) caused contraction and process retraction in quiescent cerebral cortical astrocytes effects which were blocked by 5 µM concentrations of Y27632. Conclusion: These data suggest that autoantibodies in adult diabetes having primary open angle glaucoma (glaucoma suspects) and/or dementia inhibit neurite outgrowth and promote a reactive astrocyte morphology by a mechanism which may involve activation of the RhoA/p160 ROCK signaling pathway.